2018
DOI: 10.1177/1540796918778293
|View full text |Cite
|
Sign up to set email alerts
|

Family Perspectives on the Appeals of and Alternatives to Sheltered Employment for Individuals with Severe Disabilities

Abstract: Although calls to expand integrated employment opportunities have permeated recent legislative and policy initiatives in the United States, substantial numbers of adults with severe disabilities still work in segregated settings. We examined findings from events held in eight communities to solicit the views of parents and other family members ( n = 93) on the state’s shift from sheltered to integrated employment. Our interest was in understanding what maintained their attraction to segregated work settings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Implicitly, this mapping of preferences should support individuality and flexibility in the transition. This is in line with Carter et al (2018) who found that reasons behind sheltered employment are highly individual from a family member perspective and that there is no single explanation for seeking sheltered employment. One vital prerequisite for reflecting on preferences seems to be the opportunity to try out different work placements.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Implicitly, this mapping of preferences should support individuality and flexibility in the transition. This is in line with Carter et al (2018) who found that reasons behind sheltered employment are highly individual from a family member perspective and that there is no single explanation for seeking sheltered employment. One vital prerequisite for reflecting on preferences seems to be the opportunity to try out different work placements.…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies show that employees working in competitive settings with support and in sheltered settings experience a sense of self‐efficacy, relatedness (Garrels & Sigstad, 2019) and find that sheltered employment can be satisfying (Rustad & Kassah, 2020). Sheltered employment may contribute to inclusion in social networks, provide daily structure (Carter et al, 2018; Olsen, 2009), safety, individualised attention (Carter et al, 2018) and a sense of meaningfulness (Olsen, 2009). However, people with intellectual disabilities desire to work in integrated settings (Rustad & Kassah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Carter et al (2018) found in their community conversation research that despite an overall preference for CIE, many of the individuals and families who chose segregated options did so based on concerns about economic considerations, safety, job stability, and other factors. Individuals and families make decisions about their career pathways and goals based on a wide range of factors—and a plurality continues to choose sheltered workshops despite compelling research recommendations to the contrary (Carter et al, 2018; Migliore et al, 2008). However, our review presents evidence that these decisions are made without all pertinent information about long‐term benefits of CIE relative to segregated alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…These additional benefits cannot be understated when engaging with individuals with intellectual and developmental disabilities and their families in planning career goals and supporting job search and development. Carter et al (2018) found in their community conversation research that despite an overall preference for CIE, many of the individuals and families who chose segregated options did so based on concerns about economic considerations, safety, job stability, and other factors. Individuals and families make decisions about their career pathways and goals based on a wide range of factors—and a plurality continues to choose sheltered workshops despite compelling research recommendations to the contrary (Carter et al, 2018; Migliore et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation